Maintenance of homeostasis by TLR4 ligands - Oda, Masataka; Yamamoto, Hirofumi; Kawakami, Takashige (Frontiers in Immunology, 2024)
Immunotherapy is renowned for its capacity to elicit anti-infective and anti-cancer effects by harnessing immune responses to microbial components and bolstering innate healing mechanisms through a cascade of immunological reactions. Specifically, mammalian Toll-like receptors (TLRs) have been identified as key receptors responsible for detecting microbial components. The discovery of these mammalian Toll-like receptors has clarified antigen recognition by the innate immune system. It has furnished a molecular foundation for comprehending the interplay between innate immunity and its anti-tumor or anti-infective capabilities. Moreover, accumulating evidence highlights the crucial role of TLRs in maintaining tissue homeostasis. It has also become evident that TLR-expressing macrophages play a central role in immunity by participating in the clearance of foreign substances, tissue repair, and the establishment of new tissue. This macrophage network, centered on macrophages, significantly contributes to innate healing. This review will primarily delve into innate immunity, specifically focusing on substances targeting TLR4.